The Impact of Customer Mistreatment on Employee Displaced Aggression: The Moderating Effect of Interpersonal Sensitivity and Moral Identity - Liu, Fang; Chen, Gang; Liu, Yu (Frontiers in Psychology, 2020)
Although customer mistreatment produces harmful consequences for employees and organizations, our understanding of the boundary conditions of customer mistreatment has largely been neglected. This study examines whether and when customer mistreatment influences employee displaced aggression by demonstrating interpersonal sensitivity and moral identity traits as two critical boundary conditions. Through the analysis of 623 employees’ questionnaire data, the results showed that customer mistreatment was positively related to employee displaced aggression. Further, interpersonal sensitivity has a positive moderating effect on the relationship between customer mistreatment and employee displaced aggression, while moral identity has a negative moderating effect.